High internal phase emulsion template stabilized by a piperazinyl based emulsifier and its application in preparing flexible porous polymer - Gao, Donghui; Chen, Huishan; Huang, Zhikun; Pang, Shishi; Jiang, Feng (Journal of molecular liquids, 2024)
•An emulsifier containing acylamino, secondary, and tertiary amines as its weak hydrophilic units was synthesized.•The synthesized emulsifier showed good emulsifying property than Span 80.•The porous polymer with good mechanical property and oil absorbability was prepared. The limited effectiveness of emulsifiers with suboptimal emulsification capabilities and low reactivity constrains their use in creating porous polymers through the high internal phase emulsion templating method. In this research, we synthesized a piperazinyl-based emulsifier (EA/AEP) featuring acylamino, secondary, and tertiary amines as its hydrophilic components, through a straightforward amidation process. This emulsifier was subsequently employed to stabilize HIPEs and to fabricated porous polymers. In comparison to Span 80, the use of EA/AEP enabled the formation of HIPEs with superior viscosity and stability at the internal phase volume fractions with between 75% and 95% by incorporating 25% EA/AEP. Scanning Electron Microscopy (SEM) revealed the polymers’ well-defined structures and an interconnected network of pore throats. The improved mechanical properties and oil absorbency of the polymers confirmed their structural robustness. Our approach to developing EA/AEP offers valuable insights for designing innovative emulsifiers, while the inclusion of reactive groups in its structure opens up avenues for further chemical modifications.